Quasi-experimental study to assess the effectiveness of mental health programme on promoting mental health characteristics among adolescents in Coimbatore, India - M. Baskaran; Usha Sekar; N Kokilavani (Elsevier, 2023)
Introduction: The future and progress of a country is dependent on the children today. The advent of social media has been a double-edged sword by the way it has brought us closer and also resulted in anonymous ways of mental distress to children, which is already being tested by violent school environments and pressure to succeed resulting in the prevalence of different mental illness. Parents and school authorities should ensure that their children grow and thrive in the best and safest environment possible. Aim: To evaluate the effectiveness of a Mental Health Programme on promoting mental health characteristics among adolescents in a school located in Coimbatore. Method: A quasi experimental one group pre-test and post-test design was adapted for the study. A sample of 195 students were selected using stratified random proportionate sampling technique and made to answer the pre-test questionnaire followed by the mental health programme intervention. They were then made to answer the post-test questionnaire and the data was analysed. The data collection was initiated on June 2015 and ended on October 2016, the entire process took approximately 48 weeks excluding holidays and examinations. Result: The pre-test mean score was 8.35 ± 3.02 and the post-test mean score was 26.77 ± 2.94 with a mean gain score of 18.42. The calculated paired 't' produced at value 62.278 which was found to be statistically highly significant (p < 0.001). Conclusion: The results of the present study concluded that the mental health promotion programme was effective in improving the mental health characteristics among adolescent children.